Community-dwelling elderly: ineffective management of drug regimen and risk fall - Costa, Tânia (2014)
Introduction: Drugs intake is common in the elderly, but pharmacodynamics/pharmacokinetic changes associated with multiple pathologiy amplifys the drug interactions and adverted effects. Objectives: Evaluate the management of drug regimen for the elderly residing at home (N=37), relating it to falls. Methods: Data collection was carried out by semi-structured interview (using instruments validated for the Portuguese reality) followed by descriptive/inferential analysis. Insured informed consent. Results: Average of drug ingestion was 6 drugs/day(min:2 /max:6) and 7 pills/day (min:2 /max:15),. A total of 9 prescribers were described: family physician (N=32), the hospital physician (N=26), the pharmacist (N = 6) and the elderly (N = 6). The reasons why we found that 25 elderly do not meet treatment as prescribed, was due to forgetfulness (68 %) and switching medications (23%). The management of medication regimen presents statistically significant differences compared to moderate/high risk of falling (þ=0.030), dependence in activities of daily living (þ=0.008), geriatric depression (þ=0.022), number of pills/day (þ=0.006) and number of diferent drugs (þ=0.009). The risk of falling, in other way, is related to cognitive impairment (þ=0.032), dependence in instrumental activities of daily living (þ=0.005) and number of pills/day (þ=0.043). Conclusion: Data seem indicate that there is a proportional relationship between fall risk and ineffective management of medication regimen. Considering the prevalence of falls in the elderly and it’s repercussions, highlights the need to implement nursing care of proximity/partnership, but also, integrals and integrated in both diagnoses, especially in the context of primary health care.